2015
DOI: 10.1088/0004-637x/814/2/150
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Photoionization-Driven Broad Absorption Line Variability

Abstract: We present a qualitative analysis of the variability of quasar broad absorption lines using the large multi-epoch spectroscopic data set of the Sloan Digital Sky Survey Data Release 10. We confirm that variations of absorption lines are highly coordinated among different components of the same ion or the same absorption component of different ions for C IV, Si IV, and N V. Furthermore, we show that the equivalent widths (EWs) of the lines decrease or increase statistically when the continuum brightens or dims.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
119
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 69 publications
(133 citation statements)
references
References 78 publications
(146 reference statements)
11
119
3
Order By: Relevance
“…Coordinated BAL variability over a large velocity interval (e.g., greater than ∼10 000 km s −1 ) is more easily explained by situations involving an ionization change; such behavior in the transverse-motion scenario would require coordinated motions of gas that would presumably exist at a large range of distances from the SMBH (see e.g., Hamann et al 2011;Capellupo et al 2013;Grier et al 2015;Wang et al 2015). Fig.…”
Section: Evidence For Ionization Changesmentioning
confidence: 99%
“…Coordinated BAL variability over a large velocity interval (e.g., greater than ∼10 000 km s −1 ) is more easily explained by situations involving an ionization change; such behavior in the transverse-motion scenario would require coordinated motions of gas that would presumably exist at a large range of distances from the SMBH (see e.g., Hamann et al 2011;Capellupo et al 2013;Grier et al 2015;Wang et al 2015). Fig.…”
Section: Evidence For Ionization Changesmentioning
confidence: 99%
“…While variability in BAL trough strengths is relatively common, large (>50%) changes in the absorption equivalent width is quite rare (e.g., Hall et al 2011). A primary question in BAL variability studies has been whether observed changes in BAL trough strengths are primarily due to changes in the ionization state of the outflowing wind (e.g., Wang et al 2015), or whether they are due to high column density BAL clouds moving through our line of sight (e.g., McGraw et al 2015).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, cases where variations in the observed flux and in the absorption lines are correlated, are consistent with changes in the ionization state of gas (e.g. Wang et al 2015. Cases where the trough varies simultaneously at a wide range of outflow velocities can also be explained by this scenario (Hamman et al 2011, even if there is no information on the flux variability of the central source.…”
Section: Introductionmentioning
confidence: 89%